Clube de ciências de Cametá: histórias (re)escritas para a educação científica e formação docente - PINA, Eridete Arnaud de (Universidade Federal do Pará, 2021)
In this qualitative research, of narrative approach, i investigate formative experiences lived by the participants of the Clube de Ciências de Cametá (Cametá's Science Club), created on the early 90’s. This epistemological option of research has given me theoretic and methodological conditions to investigate the experience, which history of this educative space, i organize by the rescue of memories of it’s members, the ones which i pass to analyse through the Textual Discursive Analysis, which permits me, by the means of similarity and recurrences to analyse the senses and meanings of the experiences lived by the research collaborators. I seek to investigate to understand in what terms formatives experiences lived in a Science Club, can contribute for a scientific education, to teacher’s formation and boost the (re) nucleation of a educative space with that goals. I analyse the experiences related and their contributions for the scientific education and docent formation , looking for boost the (re) nucleation of a space of juvenile child's scientific initiation and teacher formation in Science. The memorialistic reports provides us too, rebuild/systematize the history of Cametá’s Science Club and discuss analytically five emergent categories: i) New/Another vision of teaching; ii) Movements of Teacher Formation; iii) Continuous formation of basic education to beyond the Club’s wall; iv) Teaching with research: course to scientific initiation; v) Teaching Experiences that can be redefined/rebuilt for the Schools today. By the done analysis, i conclude that of the experiences in the Club can be evidenced as principles of teacher formation principles and for scientific education, turned on the development of critical thinking as facilitator for scientific literacy, and that formative experiences, can serve as base for a (re) nucleation work of a formative space for students and science teachers. Inserted to this dissertation, is the educational product “Once upon a time the Cametá’s Science Club”, a e-book in what i relate briefly about the history of the Cametá’s Science Club, i present examples of developed activities by the Club and by the school which that can serve as model and encourage for making classroom research that can be developed under the school space today and i give forwarding and suggestions for creation of Science Clubs in Schools of Basic Education.